Empowering Veterinarians to Be Planetary Health Stewards Through Policy and Practice - Kiran, Dilara; Sander, William E.; Duncan, Colleen (Frontiers in Veterinary Science, 2022)
Veterinarians are established public health professionals, committing to promote public health when they take their veterinary oath. The issue of climate change and its impact on planetary health is vital to public health, and therefore, it is critical that climate change is regarded as within the veterinary scope of practice. However, climate change is a multi-faceted issue which requires interdisciplinary collaboration and integrated stakeholder involvement in order to establish effective solutions and impactful policies. As a result, in this perspective, we discuss how policy is critical to support veterinarians in the climate change space and argue that more explicit support is needed for veterinarians to take an active role in climate change adaption, resilience, and mitigation. We address the discrepancies between the human health and veterinary professions with respect to providing policy support and capacity for practitioners to be stewards to promote planetary health and shed light on the lack of veterinary capacity in this area. We stress that veterinary professional societies are well equipped to bolster their policies, expand education for veterinary professionals and students in policy and advocacy, and establish calls to action to address climate change and planetary health issues. Ultimately, as public health professionals, veterinarians are uniquely poised to be contributors to climate change solutions and they should be actively involved in policy decision-making and empowered to take active roles in interdisciplinary conversations surrounding this important issue.